Splenic scintigraphy for further differentiation of unclear 68Ga‐DOTATOC‐PET/CT findings: Strengths and limitations. Issue 3 (17th May 2016) - Werner, Christoph; Winkens, Thomas; Freesmeyer, Martin
Summary: Splenic scintigraphy has been described to be a powerful tool in unclear 68 Ga‐DOTATOC‐PET/CT findings, allowing differentiation between somatostatin receptor (Sst)‐positive tissue deriving from neuroendocrine tumour (NET) and functioning splenic tissue. However, our own experiences sometimes show a lack of identification on splenic scintigraphy, especially in small lesions, leading to uncertainties regarding the safe identification of NET or splenic tissue. Here, we report on 10 cases with 68 Ga‐DOTATOC‐PET/CT and 99m Tc‐heat‐denaturated red blood cell (HDRBC) scintigraphy and we illustrate the strengths and limitations of 99m Tc‐HDRBC scintigraphy in this context.